Perspectives of science teaching: Comparison between western Australian teachers and Malaysian teachers - Sulaiman, Tajularipin; Abdul Rahim, Suzieleez Syrene (The International Journal of Learning, 2009)
Vision 2020 hopes to turn Malaysia into a developed country driven by industrial and agricultural sector by the year 2020. To achieve this aspiration, the manpower of the country must be developed and furnished with strong technological, mathematical and science backgrounds as early as the primary level. Effective teaching influences the attitude of the students towards science and if Malaysia hopes to develop in accordance with Vision 2020, this issue is critical. In developed countries like Australia, the teaching of science is developed humanistically to attract students to science. The approaches and methods employed by science teachers are important as there is a close relationship between the teachers’ classroom practices and student learning. Therefore, it is critical to investigate the teaching approaches and methods that are employed by teachers. This paper discusses findings of a qualitative study carried out to compare the perspectives of science teachers from Malaysia and Western Australia, focusing on two main research questions. The first question is “What are the characteristics of a science teacher?” and the second question is “What are the teachers’ perspectives of science teaching?” The participants of the study were twelve primary science teachers in Western Australia and twelve primary science teachers from Malaysia. The data collection approaches employed were an open-ended questionnaire, observation techniques, and documentation collection. The findings indicated four definitions of a science teacher, thirteen characteristics of a good science teacher and three definitions of science teaching.